Hubungan Antara Kestabilan Emosi Dengan Kontrol Diri Pada Atlet Beladiri Kota Surakarta - Maulana, Muhammad Yudistira Arya, Achmad Dwityanto, S.Psi, M.Si (2017)
At the time face his opponent in the arena the game, a professional athlete will tries to show her best performance, upon the ability, and bring techniques he had learned for exercise. Performance the athlete will also greatly influenced by the opposed to he faced, including emotion will appear during the match was going. Negative emotions of anger can surface at an athlete as his opponent make the the athlete as target of defence. Tendency which happens is that an athlete will be more sensitive and easily provoked to counter when his face has been punched by the opponent. Besides, it can appear if an athlete has been conceded since the beginning of the match, moreover if that athlete feels that all attacks done by him are not considered not hitting the opponent by referee. The occurrence of another on the is on a wrestling match in a pound xix west java 2016 tinged the unrest, monday ( 9 / 26 / 2016 ).The game at gor saparua, bandung city this, started protest by players wrestling east kalimantan, ardiansyah, who feel i must defend two points but are being 1 points by a grand jury.Feel protest players not ignored, turn coach kaltim who protests.The east kalimantan in, and struck the referee from iran because they did not victory decisions who won athletes west java in the class 65 kg (http://www.arah.com). This research objective is to determine the relationship between emotional stability and self-control on martial-art athletes of Surakarta, emotional stability degree and self-control, and to find the effective contribution of emotional stability toward self-control. This research is correlational research. This research subjects are martial-art athletes from six self-defense branch (karate, kempo, taekwondo, judo, silat) who have joined provincial-level match of 100 people, taken from 156 people of population by using sampling technique that is purposive sampling. Instrument used in this research is the scale to determine emotional stability and self-control. As for the method used is questionnaire by using measuring instrument such as scale of emotional stability and scale of self-control. The result is hypothesis testing by using product moment correlation technique. The analysis resulted in rxy =0,733 with P=0,000 (P>0,01) showing that there is significantly positive correlation between emotional stability and self-control. It means that the higher emotional stability leads to higher self-control. Otherwise, the lower emotional stability, then the lower self-control is. The empirical mean of emotional stability variable is amount of 60,40 and hypothetic mean is amount of 45. It shows that empirical mean > hypothetic mean that illustrates that In general an athlete fighter the city of surakarta have high emotional stability. Further the empirical mean of self-control variables is amount of 72,69 and hypothetic mean is amount of 55. It shows that empirical mean > hypothetic mean that illustrates that In general an athlete fighter the city of surakarta have high self-control. The role of the emotional stability toward self-control is amount of 53,7% that means there is still 46,3% that self-control affect. Keywords: emotional stability, self-control, martial-arts athlet